1994
DOI: 10.1055/s-2008-1073043
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Optic Pathway Gliomas in Children with Neurofibromatosis Type 1

Abstract: Optic pathway gliomas (OPG) are found in about 15% of patients with neurofibromatosis Type 1 (NF-1). The natural history of OPG is not yet well documented. Treatment in cases with growing tumors is still controversial. Twenty-one patients with NF-1 and OPG, diagnosed over a 20-year period, and followed neuroradiologically and ophthalmologically for at least two years, were reevaluated. The diagnosis of OPG was made at a mean age of 7.1 years (range 0-14.5 years); six children were asymptomatic, 15 were symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 21 publications
3
37
0
3
Order By: Relevance
“…Four of the 43 patients with an intracranial tumour developed a second tumour during the follow-up period. More than half of the cohort described by Kuenzle et al [19]developed a second tumour during 9 years of follow-up, and Hochstrasser et al [11]and Sørensen et al [20]found second tumours in 21 and 47%, respectively, of children with NF. Direct comparison of these studies with our cohort is difficult because of the differences in follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the 43 patients with an intracranial tumour developed a second tumour during the follow-up period. More than half of the cohort described by Kuenzle et al [19]developed a second tumour during 9 years of follow-up, and Hochstrasser et al [11]and Sørensen et al [20]found second tumours in 21 and 47%, respectively, of children with NF. Direct comparison of these studies with our cohort is difficult because of the differences in follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Kuenzle et al [19]described 21 such children, of whom 11 were found to have a cerebral tumour during a follow-up period of 9 years. Hochstrasser et al [11]studied a group of 133 NF children, of whom 24 had intracranial tumours, of which 20 were optic gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…But more than 50% of the patients have very indolent or no progression of the disease, thus they do not need treatment. A nonprogressive evolution is more likely to occur in children with NF1 [9]. This phakomatosis is present in up to 50% of children with OPHG.…”
Section: Discussionmentioning
confidence: 99%
“…35) Even partial resection of the tumor with palliative decompression of the eloquent structures can lead to regress of symptoms. 3,10) However, in cases of intrinsic chiasmatic gliomas the role of surgery is usually limited to verification of histologi cal diagnosis, 1,4,6,9,15) whereas chemotherapy and/or irradiation are considered to be the main treatment options. Such approaches can provide stabilization or improvement of vision in 88.993% of pa tients, 2,13) but complete restoration of visual func tions is very unusual.…”
Section: Discussionmentioning
confidence: 99%